(untitled) (Marketing Journal, 2025)
This article provides a scientific analysis of digital transformation processes in the automotive industry, the development of marketing technologies, and their impact on sales performance. The study highlights the mechanisms of online decision -making by car buyers, the digital tools used in dealership centers, and the influence of modern technologies on market competitiveness.